PENGARUH PEMBERIAN BAWANG PUTIH TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Hypertension is the silent disease because people do not know they have hypertension before checking their blood pressure. Non-pharmacological treatment of hypertension can use herbal plants, such as garlic. The purpose of this study was to determine the effect of steeping garlic on blood pressure in patients with hypertension This research is limited from 2009 to 2022 and gets 9 eligible articles sourced from the Google Scholar search engine with the keywords “garlic, blood pressure AND hypertension. The results of the study reported that from 9 articles it was found that garlic was effective in lowering blood pressure in patients with hypertension.